The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/etc.3205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of microbial communities for candidate indicators of multiple metal impacts in marine sediments from northern Australia

Abstract: Coastal sediments accumulate metals from anthropogenic sources and as a consequence industry is required to monitor sediment health. The total concentration of a metal does not necessarily reflect its potential toxicity or biological impact, so biological assessment tools are useful for monitoring. Rapid biological assessment tools sensitive enough to detect relatively small increases in metal concentrations would provide early warning of future ecosystem impact. The authors investigated in situ populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 59 publications
(70 reference statements)
2
2
0
Order By: Relevance
“…2). This is consistent with biogeographic surveys that have detected this group in anoxic estuarine sediments (unpublished data, accession number: JN672646), OMZs (unpublished data, accession number: MG875625), and marine sediments [79]. However, the DEV007 clade is also found in oxic seawater attached to particles [35].…”
Section: Discussionsupporting
confidence: 87%
“…2). This is consistent with biogeographic surveys that have detected this group in anoxic estuarine sediments (unpublished data, accession number: JN672646), OMZs (unpublished data, accession number: MG875625), and marine sediments [79]. However, the DEV007 clade is also found in oxic seawater attached to particles [35].…”
Section: Discussionsupporting
confidence: 87%
“…SAR324 and SAR406 are considered oligotrophic bacteria (Cho and Giovannoni, 2004), which could also explain an adaptation toward low levels of trace metal concentrations. Consistent with our findings, the Verrucomicrobia DEV007 was recently identified among the most sensitive taxa to multiple metals in a molecular screening of microbial communities for candidate indicators of multiple metal impacts performed in marine sediments from northern Australia (Cornall et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…However, we observed that the proximity to the aquaculture site was associated with the reduction of the Verrucomicrobia uncultured family DEV007 in the limpet microbiome of limpets. DEV007 is a marine group of bacteria recently pointed out as particularly sensitive to metal pollution in surface waters and marine sediments [68,69]. Its decrease in limpets growing in adhesion to the aquaculture cage might be related to the increase in heavy metal accumulation that often accompanies aquaculture practices [1], which can indirectly affect the most sensitive species in the microbiome of nearby wild organisms.…”
Section: Discussionmentioning
confidence: 99%